Estudio de correlación de las variables significativas analizadas en el censo económico 2010 - Álvarez Guale, Raúl (2011)
This article presents a study of correlation analysis about the most significant variables presented by the National Institute of Statistics and Census of economical census in 2010. The study makes focus using the linear correlation of Pearson and it is pretended to eliminate nonsense correlations found in this analysis by the use partial correlations.